الاقتصاد الأخضر كنموذج بديل لتحقيق التنمية المستدامة - عرض تجارب دولية رائدة - - كافي, فريدة; هماش, لمين (Université de M'sila, 2017)
The world has recently witnessed a great interest in environmental affairs, where the protection of the environment and the preservation of one of the most important features of the new international order so it was necessary to emerge a new economic development that means and be a model of economic development and rapid growth so has emerged a new concept on the international arena The green economy to incorporate environmental considerations at each stage of production and consumption and formulate policies to correct economic and social imbalances and reduce environmental degradation. This research paper examines how many countries seek to adopt green economy policy to re-shape and correct economic activities to be more conducive to the environment and support economic and social development in order to achieve sustainable development goals.
Keywords: green economy; environmental protection; sustainable development